A Study of Serum Adiponectin Levels in Patients with Polycystic Ovarian Syndrome and its Correlation with Various Cardiometabolic Risk Markers - G. Surendra Prasad; Uma Kaimal Saikia; Ashok Krishna Bhuyan; Abhamoni Baro (Journal of Human Reproductive Sciences)
Background: Polycystic ovarian syndrome (PCOS) is the most common metabolic disorder in the reproductive age group, the pathogenesis of which is constantly evolving with the discovery of novel molecules and the lookout for potential therapeutic targets. Aims: The aim of the present study was to estimate the circulating levels of serum adiponectin in patients with PCOS compared to controls and to find its correlation with markers of cardiovascular risk, with special emphasis on circulating levels of oxidised low-density lipoprotein (oxLDL). Settings and Design: In this cross-sectional observational study recently diagnosed, PCOS subjects were compared with age- and body mass index (BMI)-matched controls. Materials and Methods: All the included subjects underwent detailed clinical, biochemical and hormonal evaluation, including lipid profile, 75 g oral glucose tolerance test, fasting serum insulin, fasting serum adiponectin, oxLDL, total testosterone and anti-Mullerian hormone. Statistical Analysis Used: Appropriate statistical methods were performed using SPSS (version 21) and Microsoft Excel (2019). Results: A total of 56 PCOS cases and 32 controls were included in the study. Mean values of serum adiponectin (μg/mL) in our study were found to be significantly lower in PCOS cases (11.53 ± 4.74) versus controls (14.73 ± 5.61) irrespective of BMI. Mean values of serum oxLDL (μg/dL) were found to be higher in PCOS cases (157.96 ± 53.89) versus controls (117.52 ± 45.44), with a significant negative correlation between adiponectin and oxLDL in cases. No difference in levels of adiponectin was found between the different PCOS phenotypes. Conclusion: Hypoadiponectinaemia was found to be associated with PCOS irrespective of obesity in PCOS subjects. Serum oxLDL can complement adiponectin as early predictor of CV risk in PCOS.